PENGARUH KARAKTERISTIK PEKERJAAN, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN LARISSA AESTHETIC CENTER SEMARANG - Epy Rupiningsih, 14.05.51.0072; Rijanti, Tristiana (Students Journal of Economic and Management, 2018)
The purpose of this research is to analyze the influence of job characteristics variable, work discipline and work motivation to job satisfaction of employee of Larissa Aesthetic Center Semarang. Respondents of this research are employees of Larissa Aesthetic Center Semarang who have worked for more than 2 years as many as 77 people. Sampling technique using sampling census method, then analyzed by using multiple linear regression. Data from the questionnaires were tested with validity, reliability and multiple regression tests. The results of his research are: (1) job characteristics have a positive effect on employee job satisfaction. (2) discipline has positive effect on employee job satisfaction. (3) motivation has not positive effect on employee job satisfaction.Keywords: job characteristics, discipline, motivation and employee job satisfaction.